DYSTOCIA DUE TO MONOCEPHALUS TETRABRACHIUS TETRAPUS THORACO-PAGUS DICAUDATUS MONSTER IN BUFFALO - KUMAR, SANDEEP; SUNDER, SHYAM; DUTT, RAVI; SINGH, GYAN; PANDEY, A K; SINGH, KULDEEP (The Indian Journal of Animal Reproduction, 2011)
A buffalo suffering from fetal dystocia was examined and delivery of monocephalus tetrabrachius tetrapus thoraco-pagus dicaudatus monster by caesarean section is reported.
Keywords: MONOCEPHALUS; TETRABRACHIUS; TETRAPUS; THORACO-PAGUS; DICAUDATUS